Rozwiązane

POTRZEBUJE POMOCY NA JUŻ



POTRZEBUJE POMOCY NA JUŻ class=

Odpowiedź :

Odpowiedź:

a)

2(x - 1/2) - x + 3 = 3

2x - 1 - x + 3 = 3

x + 2 = 3

x = 3 - 2 = 1

b)

0 = x - 1 - (3x - 5)

x - 1 - 3x + 5 = 0

-2x = - 4      /:(-2)

x = 2

c)

-1/2x + 1 + 3x/2 = 3

-1/2x + 1 1/2x = 3 - 1

x = 2

d)

3(1 - x) - (1 - 2x) = 9

3 - 3x - 1 + 2x = 9

-x = 9 - 2     /*(-1)

x = -7

Szczegółowe wyjaśnienie:

Odpowiedź:

a)

2(x - 1/2) - x + 3 = 3

2x - 1 - x + 3 = 3

x + 2 = 3

x = 3 - 2 = 1

b)

0 = x - 1 - (3x - 5)

x - 1 - 3x + 5 = 0

-2x = - 4  /:(-2)

x = 2

c)

-1/2x + 1 + 3x/2 = 3

-1/2x + 1 1/2x = 3 - 1

x = 2

d)

3(1 - x) - (1 - 2x) = 9

3 - 3x - 1 + 2x = 9

-x = 9 - 2 /*(-1)

x = -7

Szczegółowe wyjaśnienie:

Mam nadzieję że pomogłam i liczę na naj :)